Pengenalan teknologi dan strategi dalam pemanfaatan limbah pelepah pinang menjadi produk kreatif di Gampong Lamtamot Kabupaten Aceh Besar (Introduction to technology and strategy in the utilization of areca nut leaf waste into creative products in Lamtamot Village, Aceh Besar District) - Ramli, Ichwana; Syafriandi, S; Ratna, R; Achmad, Ashfa (Buletin Pengabdian, 2023)
The community of Lamtamot Village makes agriculture and plantations their primary income, especially areca nut plantations. The community has not used areca nut leaf waste to be used as products. The purpose of this paper was to determine the knowledge and sustainability of the utilization of areca nut leaf sheaths into creative local products and can increase household income for the community of Lamtamot Village. The activity began with distributing questionnaires before service activities (pre-test), socialization, distributing questionnaires after socialization activities (post-test), testing tools, and promotions. The results of the evaluation showed an increase in the level of knowledge and understanding of areca nut farmers and the community regarding the utilization of areca nut leaf sheaths into products that can be used and marketed. The highest moisture content test result on the areca nut leaf sheaths to be printed was 16.04%. In comparison, the lowest moisture content was 9.7%. The ideal leaf sheaths for printing were 12-16%. The next step was the testing of the areca nut leaf sheaths printing tools (machine manufacturer and plate production) to be able to form plates and curves as packaging. The community can operate the machine because the machine was very simple even though it uses a manual jack. The pre-test results from the questionnaire showed that 84 % of the respondents had no knowledge regarding the utilization of areca nut leaf sheaths. After completing the introduction of tools and explanations, 92% of the respondents already have knowledge of the utilization of the areca nut leaf sheath treatment, and 32% have the desire to develop an areca waste processing business. Products marketing is carried out online, supported by the ability of the public to access e-commerce accounts.